DISENTANGLING THE ROLE OF PHENOTYPIC PLASTICITY AND GENETIC DIVERGENCE IN CONTEMPORARY ECOTYPE FORMATION DURING A BIOLOGICAL INVASION. (1st September 2014) - Lucek, Kay; Sivasundar, Arjun; Seehausen, Ole
Abstract: The occurrence of contemporary ecotype formation through adaptive divergence of populations within the range of an invasive species typically requires standing genetic variation but can be facilitated by phenotypic plasticity. The relative contributions of both of these to adaptive trait differentiation have rarely been simultaneously quantified in recently diverging vertebrate populations. Here we study a case of intraspecific divergence into distinct lake and stream ecotypes of threespine stickleback that evolved in the past 140 years within the invasive range in Switzerland. Using a controlled laboratory experiment with full‐sib crosses and treatments mimicking a key feature of ecotypic niche divergence, we test if the phenotypic divergence that we observe in the wild results from phenotypic plasticity or divergent genetic predisposition. Our experimental groups show qualitatively similar phenotypic divergence as those observed among wild adults. The relative contribution of plasticity and divergent genetic predisposition differs among the traits studied, with traits related to the biomechanics of feeding showing a stronger genetic predisposition, whereas traits related to locomotion are mainly plastic. These results implicate that phenotypic plasticity and standing genetic variation interacted during contemporary ecotype formation in this case.